2019
DOI: 10.3390/en12030398
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition Effect of Gas–Solid Two-Phase Inhibitors on Methane Explosion

Abstract: In order to study the inhibition effect of gas-solid two-phase inhibitors on a methane explosion, the influence of these parameters was investigated and compared with that of single-phase inhibitors. The results show that the inhibition effect of gas-solid two-phase inhibitors on a methane explosion is better than the added effect of two single-phase inhibitors, indicating that a synergistic effect can be obtained by gas-solid two-phase inhibitors. The two-phase inhibitors which are composed of NaHCO 3 (BC) po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Equation (10) gives an expression to calculate oxygen mass fraction as a function of ventilation mass rate, discharge mass rate, and discharge time.…”
Section: Discharge Mass Rate Of Inert Gas Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (10) gives an expression to calculate oxygen mass fraction as a function of ventilation mass rate, discharge mass rate, and discharge time.…”
Section: Discharge Mass Rate Of Inert Gas Agentsmentioning
confidence: 99%
“…Some research [9] has been carried out to investigate the application of inert gas agents in some typical buildings for disabled persons, elderly in nursing homes, and other citizens with reduced cognitive function, etc. Inert gas agents also have great potential as inhibitors of gas explosions by reducing or possibly eliminating the risk of explosions [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A 20 L explosion vessel is commonly used to study the explosibility of dust or combustible gases [26][27][28]. Figure 6 shows the explosion pressure history of coal dust measured at a concentration of 250 g/m 3 , and indicates two parameters used to evaluate the explosibility of dust: P max and (dP/dt) max .…”
Section: Explosion Severity Of Mixed Dust Cloudmentioning
confidence: 99%
“…The results showed that the injection of nitrogen and ABC powder has an obvious inhibitory effect on the explosion overpressure and flame propagation velocity. Wang et al 22 studied the effect of a gas–solid two-phase inhibitor on gas explosion. The results showed that an inhibitor composed of NaHCO 3 (BC) powder/inert gas had better inhibition performance in comparison to an inhibitor composed of NH 4 H 2 PO 4 (ABC) powder/inert gas.…”
Section: Introductionmentioning
confidence: 99%